Sosialisasi Ketentuan Kredit Macet Persepektif Resiko Kreditur Atas Jaminan Yang Bukan Milik Debitur - Tito Malindo (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
This article discusses the socialization of provisions on bad credit from the perspective of creditor risk on collateral that does not belong to the debtor in Mojokerto City. This research was conducted through strategic steps including identifying community needs, developing informative socialization materials, and implementing educational activities. The results of the survey and interviews showed low public understanding of creditor risk and the importance of valid collateral. The socialization program designed with simple language and educational materials such as brochures and short videos succeeded in increasing public awareness. Evaluation through focus group discussions (FGD) revealed the need to increase interaction and consistency in socialization. In addition, supporting studies showed the importance of supervision, coaching, and prevention efforts to overcome bad credit. With suggestions to increase the frequency of socialization programs, utilize social media, and involve banking practitioners and legal experts, it is hoped that it can increase public understanding and reduce the number of bad credit, as well as support financial stability in Mojokerto City.